De l’antisémitisme au fascisme en Roumanie: naissance du Roumain nouveau régénéré par la révolution de droite - Sandu, Traian (2008)
Abstract: The adaptation of the “new consensus” about fascism to Romanian Iron Guard has already given some brilliant results as far as political modelling is concerned. Time has come to investigate patiently the historical documents in order to evaluate the degree of consciousness of the contemporary people about the revolutionary project of the Romanian Fascism and about its practices which intended to replace traditional life in agrarian orthodox Romania by a new social life modeled in the legionary nests. As this new life is structured around the adoration of the charismatic personality of the “Captain” Corneliu Zelea Codreanu, his main text, For my legionaries, will be largely solicited for the passages corresponding to the early period of formation lasting from 1919 to 1927. Special attention will be devoted to the elements of breaking off with this political godfather in anti-Semitism, A. C. Cuza. Passage from traditional religious minded, but also socio-economic post-war anti-Semitis